Al Quran dan Peradaban Manusia (Membangun Peradaban Masyarakat dalam Negara) - Ahmad Ari Masyhuri (LP2M Universitas PTIQ Jakarta, 2015)
Civilization is the highest form of culture of a group of people that is distinguished significantly from other creatures, Religion (read Islam) is the most important factor that determines the characteristics of a civilization. Civilization reflects the quality of human life in society. The quality is measured by peace (human security), peace (peacefull), justice (justice), equitable welfare (welfare). The realization of economic and cultural socio-political justice will not be perfect with a haphazard agenda, but it will mature if done consciously and planned, because the State is obliged to provide equal legal services and certainty to the lives of diverse communities (diversity is Sunnatullah; QS. Al-Hujarat [49]: 13). The determination of the people to form a State Government that aims to protect the entire nation of society in one State, promote public welfare, educate the nation’s life, and participate in carrying out world order based on independence, lasting peace and social justice as stated in the opening of the 1945 Constitution essence in building and developing quality human resources, skilled human resources utilizing science and technology, cultured and moral that are rooted in religion that develops in a State. There are three forms of prosperous society which are recorded by the Qur’an and confirmed by the Ulama, the three forms have differences from each other in the characteristics, characteristics, foundation and supporting pillars that are supported (Dr. M. Ahmad Khalafallah; Hakaza Yabni al-Islam, 2008)